Clinical and radiological characteristics of hip joints in children with cerebral palsy - Lyutkevych, Mykola; Korolkov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Abnormalities of development of hip joints (HJ) in children with cerebral palsy (CP) lead to hip decentration, subluxation and dislocation. Spastic hip subluxation and dislocation is a significant problem in patients with CP and leads to significant disturbances of self-service and movement functions. Purpose: to identify patterns of development of HJ in children with CP basing upon retrospective clinical and radiographic analysis. Methods: this work is based on an analysis of 148 medical records of children with CP with hip subluxation and dislocation treated at the hospital. There were 86 boys and 62 girls among them. All patients were divided into 3 age groups (from 1 to 6 years, from 6 12 years, and from 12 to 18 years) as well as according to mode of CP: hemiparetic mode was in 24.3% of cases (36 patients), double hemiparesis (tetraparesis) - in 13.5% (20 patients), spastic diplegia - in 37.2% (55 patients), hyperkinetic mode - in 10.8% (16 patients), atonic-astatic mode - in 6.1% (9 patients), and mixed one - in 8.1% (12 patients). Concerning the level of motor activity according to the GMFCS classification all patients were divided as follows: in 61 patients (41.2%) there were marked movement disorders of the 2nd level, in 50 (33,8%) patients – the 3rd level, and in 37 (25,0%) – the 4th level. Results: dynamics of main indexes of HJ development were analyzed and direct dependence of the degree of pathological changes in HJ in children with CP on the severity of neurological and orthopedic deficit was revealed. Clinically, the most informative sign is magnitude and dynamics of limitations of hip abduction and extension (severity of hip flexion-adduction contracture) which correlates with value of migration index (MI). We strongly insist on exacerbation of orthopedic cautions in the "non walking" children (GMFCS III, IV, V) concerning development and progression of HJ pathology. The beginning of spastic hip subluxation and dislocation has usually no clinical manifestations. Examining the children with CP one must follow the principle: to define HJ abnormal until otherwise will not be proven. We recommend to make panoramic X-ray films of the pelvis in all children with CP at the age of 1 year for screening assessment of pathological changes in HJ and for further dynamic surveillance. The main attention should be paid to the analysis of the values of the MI, Wìberg’s angle (WA) and acetabular index (AI). Conclusions: clinical examination and analysis of the pelvis panoramic radiographs in children with CP allow to distinguish clinical groups and to define individual approaches to the choice of medical (including surgical) tactics and to keeping children of this category. MI clearly correlates with the femoral neck-shaft angle, AI and WA, and the dynamics of these indexes allows to use them as prognostic indicators of HJ development. Discovered anatomical and functional differences between the signs of congenital and spastic hip dislocation in children with CP have to be used in daily practice of children’s orthopedics-traumatologists and must be taken into account while planning medical therapies (conservative and/or surgical) for eliminating HJ pathology.